Peroxiredoxin 6: The Protector of Male Fertility - Cristian O'Flaherty (MDPI AG, 2018)
The spermatozoon is a terminal cell with the unique purpose of delivering the paternal genome to the oocyte during fertilization. Once spermatozoa enter into the female reproductive tract, they count on only the antioxidant protection that they received during spermatogenesis and epididymal maturation. Peroxiredoxins (PRDXs), particularly PRDX6, are important players in the antioxidant protection and regulation of reactive oxygen species (ROS) levels in spermatozoa. PRDX6, through its peroxidase and calcium-independent phospholipase A2 activities, plays a major role in the regulation of ROS to maintain viability and motility and allow the spermatozoon to achieve fertilizing ability during the complex process of capacitation. The absence of PRDX6 is sufficient to promote abnormal reproductive outcomes in mice that resemble what we observe in infertile men. Indeed, Prdx6−/− spermatozoa display low motility and severe DNA damage, which is translated into reduced ability to fertilize oocytes in vitro or produce a low number of pups compared to wild-type controls. This review focuses on the role of PRDX6 as the primary antioxidant enzyme that protects the spermatozoon from oxidative-stress-associated damages to protect the paternal genome and assure fertility.